Background Radio emissions observation at 1.42 GHz - Abood, Kamal M.; Kitas, Anmar M. (Iraqi Journal of Science, 2018)
In this work, a Radio Emission Background at 1.42 GHz; 21 cm Hydrogen line is carried out by using a 3-meter radio telescope, these telescope is placed on the roof of the building the Astronomy and Space Department at the college of Science, University of Baghdad. Background spectrometry files were received and arranged with a schedule of minimum observation time with span in (GHz). In this work, an observation program was set up to identify some variables related to the telescope and its study, including span, sweep time and central frequency using (MATLAB 2013 software) by reading four files which were selected from the dataset and in different observation times and different span.